Handbook of research on nanoscience, nanotechnology, and advanced materials - Bououdina, Mohamed, 1965-; Davim, J. Paulo (Hershey, P.A. : Engineering Science Reference, 2014)
"This book presents a detailed analysis of current experimental and theoretical approaches surrounding nanomaterials science and applications in fields such as biomedicine, renewable energy, and synthetic materials"--provided by publisher